Sputtering onto liquids: how does the liquid viscosity affect the formation of nanoparticles and metal films?. Issue 4 (22nd November 2022) - Sergievskaya, Anastasiya; Absil, Rémi; Chauvin, Adrien; Yusenko, Kirill V.; Veselý, Jozef; Godfroid, Thomas; Konstantinidis, Stephanos
Abstract : This paper reports on the effect of the solvent viscosity on the formation of gold nanoparticles (Au NPs) during the sputtering onto liquid (SoL) process. Abstract : This paper reports on the effect of the solvent viscosity on the formation of gold nanoparticles (Au NPs) during the sputtering onto liquid (SoL) process. All other parameters related to the plasma and the host liquid are kept constant. SoL is a simple highly reproducible approach for the preparation of colloidal dispersions of small naked NPs. The properties of the final product are determined by both the sputtering parameters and the host liquid characteristics. As a model system we chose to sputter a gold target by a direct-current magnetron discharge onto a line of polymerized rapeseed oils having similar surface tension (32.6–33.1 mJ m −2 at RT). It was found that well-dispersed Au NPs grow in the bulk solution of oils with low viscosities (below 630 cP at 25 °C), while a gold film forms onto the surface of high viscosity liquids (more than 1000 cP at 25 °C). The mean diameter of the individual Au NPs is in the range of about 2.1–2.5 nm according to transmission electron microscopy.